2016
DOI: 10.1039/c6np00021e
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in research on lignans and neolignans

Abstract: Covering: 2009 to 2015Lignans and neolignans are a large group of natural products derived from the oxidative coupling of two C6-C3 units. Owing to their biological activities ranging from antioxidant, antitumor, anti-inflammatory to antiviral properties, they have been used for a long time both in ethnic as well as in conventional medicine. This review describes 564 of the latest examples of naturally occurring lignans and neolignans, and their glycosides in some cases, which have been isolated between 2009 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
246
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(262 citation statements)
references
References 200 publications
2
246
0
2
Order By: Relevance
“…One of the most important coumarins found in noni plant is scopoletin (6-methoxy-7-hydroxycoumarin), which has shown a notable effect in the treatment of obesity and metabolic dysfunction [49,55]. Lignans and neolignans are present in many plants, being a large group of natural products derived from the oxidative coupling of two C6-C3 units [75]. The most important lignans isolated from noni fruit are americanin A, americanol A, episesamin 2,6-dicatechol, isoprincepin, lirioresinol, lirioresinol B dimethyl ether, morindolin, and 3,3’-bisdemethypinoresinol.…”
Section: Morinda Citrifolia Linn (Noni)mentioning
confidence: 99%
“…One of the most important coumarins found in noni plant is scopoletin (6-methoxy-7-hydroxycoumarin), which has shown a notable effect in the treatment of obesity and metabolic dysfunction [49,55]. Lignans and neolignans are present in many plants, being a large group of natural products derived from the oxidative coupling of two C6-C3 units [75]. The most important lignans isolated from noni fruit are americanin A, americanol A, episesamin 2,6-dicatechol, isoprincepin, lirioresinol, lirioresinol B dimethyl ether, morindolin, and 3,3’-bisdemethypinoresinol.…”
Section: Morinda Citrifolia Linn (Noni)mentioning
confidence: 99%
“…Plant-derived antimicrobial compounds belong to an exceptionally wide diversity of classes, including terpenoids (Bhalodia et al, 2011), lignans (Teponno et al, 2016), alkaloids and peptides (Bhatter et al, 2016), phenolic compounds (Heleno et al, 2015) and coumarins (Bhatter et al, 2015, 2016). All of the aforementioned compounds are regarded as secondary metabolism products in plants, not strictly required for their survival, but usually conferring a positive effect for its use as medicinal purposes (Harborne, 1997; Kroymann, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Plant lignans and derivatives are one of the most extensively distributed constituents in the plant kingdom 16 . Several reports have demonstrated that these compounds exhibit a wide range of biological activities including cardiovascular, antiinflammatory, antimicrobial, antiviral, anticancer, immunosuppressive, insecticidal, anti-feeding, and anti-oxidant effects 10 .…”
Section: Fig 3: Log Concentration Versus % Dpph Scavenging Effect Ofmentioning
confidence: 99%